Exploring Undergraduate Students’ Perceptions Toward Extensive Reading Course - Basri; Basikin (Formosa Journal of Sustainable Research, 2024)
The importance of extensive reading is undeniable. Through implementing extensive reading, students can obtain many benefits toward their English proficiency. Although much research has been conducted towards implementing ER, few study underlying the students’ perceptions as the subject of ER implementation. Thus, this research aims at exploring the students’ perceptions towards their ER course. Further, this research also aims at exploring the students’ outcomes gained from the ER course. This study used qualitative descriptive design, the participants in this study are undergraduate students who have experience on extensive reading course at private university in Makassar. The sampling technique used in this study was purposive sampling involving 7 participants. In-depth interview data collection technique was used in this study and the results obtained were analyzed using thematic analysis. The results show that the extensive reading course improved the students' reading fluency, reading comprehension, vocabulary acquisition, writing ability, and reading motivation, among other five areas. The way ER principles are applied throughout the training has an impact on those benefits. Easy reading materials, a variety of available materials, authority in material selection, frequent reading, speed reading, silent reading, meaningful reading, enjoyable reading, teacher direction, and the teacher as a role model are the concepts that are put into practice